INFLUENCE OF PARENTS' SOCIO-ECONOMIC STATUS AND VOCATIONAL LEARNING MOTIVATION TO LEARNING ACHIEVEMENT IN THE LESSON OF CHASSIS AND POWER TRANSDUCTOR FOR XII GRADE STUDENTS OF LIGHT VIHICLE ENGINEERING DEPARTMENT OF SMK PIRI 1 YOGYAKARTA IN ACADEMIC YEAR 2013/2014 - Indra Tri Setyawan; Tarto Sentono (Jurnal Taman Vokasi, 2014)
The purpose of the study is to find the influence of parents’ socio-economic status and vocational learning motivation to learning achievement in the lesson of chassis and power transductor for XII grade students of SMK PIRI 1 Yogyakarta in the academic year 2013/2014.This research includes ex-post facto research conducted on the population 129 students with the sample 98 students. Data collection techniques in this research uses questionnaire instrument techniques for variable of parents’ socio-economic status and vocational learning motivation whereas documentation instrument techniques uses for variable of learning achievement the lesson of chassis and power transductor. Questionnaire was tested on 25 respondents. Data analysis techniques uses partial correlation analysis and regression analysis were preceded by prerequisite test that are normality test, linearity and multikolonieritas.The results of the data analysis is (1) parents’ socio-economic status (X1) influential positive and significant on learning achievement in the lesson of chassis and power transductor, (2) vocational learning motivation (X2) influential positive and significant on learning achievement in the lesson of chassis and power transductor, (3) parents’ socio-economic status (X1) and vocational learning motivation (X2) are jointly have positive and significant effect on learning achievement in the lesson of chassis and power transductor. Positive means that the higher the value of X1 and X2, the higher the value of Y, and vice versa. Thus, the socio-economic status of parents and the motivation to study vocational subjects affecting learning achievement the lesson of chassis and power transductor XII grade students of SMK PIRI 1 Yogyakarta in the academic year 2013/2014.